Effect on the Eastern Anatolian Fault Zone Erkenek and Pazarcik Segments of the 6 February 2023 Pazarcik (Kahramanmaras) Earthquake: Observations from Celikhan-Golbasi (Adiyaman) - Aksoy, Ercan; Akgun, Elif; Softa, Mustafa; Kocbulut, Fikret; Sozbilir, Hasan; Tatar, Orhan; Erol, Serap Colak (Afet ve Acil Durum Yonetimi Baskanligi (AFAD), 2023)
This study aims to evaluate on a regional scale the surface ruptures that developed on the segments forming the southern branch of the Eastern Anatolian Fault Zone (EAFZ), on 2023 February 6, based on the morphology and slip amounts determined by mapping at 1/25.000 scale. It has in sight that the left lateral displacement, which measured 2.90 m at Celikhan, reached 3.80 m towards Golbasi/Balkar along the surface rupture and increased as close to the location of the main shock. The surface rupture developing a narrow deformation zone in Celikhan forms an extensional deformation zone by stepping to the left towards Golbasi/Balkar locality. Due to this situation, small-scale pull-apart basins have developed in the area, where vertical offsets up to 60 cm are also measured. © 2023 Universite de Paris VI (Pierre et Marie Curie). All rights reserved.
6 Şubat 2023 Pazarcık (Kahramanmaraş) depreminin Doğu Anadolu Fay Zonu Erkenek ve Pazarcık Segmentleri Üzerindeki Etkisi: Çelikhan-Gölbaşı (Adıyaman) Arasından Gözlemler
Keywords: East Anatolian Fault Zone; Pazarcik (Kahramanmaras) Earthquake; Pull-apart basin; Surface rupture